The effectiveness of 3d alkene isomerisme courseware (3D-AI) at MRSM Terendak, Melaka - Bakar, Norasiken; M. Zain, Z.R; Hisham, Syariffanor (2012)
Abstract-The usage of multimedia courseware in education field is one of the methods that can be used to increase the motivation and interest of student towards the subject that being taught. This research is about the development and effectiveness of courseware title 3 dimensional (3D) Alkenes Isomerism. This courseware is specifically developed for a topic in chemistry subject for form five students in Malaysia. The topic chosen are Alkenes and Isomerism which is a part of hydrocarbon topic in chemistry secondary syllabus. The research was done at Maktab Rendah Sains MARA Terendak Melaka involving Form five Students who took Sijil Pelajaran Malaysia (SPM) in year 2010.The questionnaires is the instrument used in this research to determine the problem statement. Based on the questionnaires, Alkenes and Isomerism are identify as the most difficult topic and suggested a courseware is developed and then tested for its effectiveness. The courseware used MAYA software version 2010 to develop the 3D molecules of Alkenes structure. Two group of students called Experimental group (EC) and Control group (CG) involved in this process and a set of questionnaires is used during pre-test and post test for this purpose. A pilot study is running to determine the effectiveness of the courseware before post test is carried out. From this research the researcher finds out that courseware titled 3 dimensional (3D) Alkenes Isomerism(3D AI) is suitable to used during teaching and learning process as teaching aid. This is also because it can help to increase student’s performance for topic Alkenes Isomerism.